POTENSI ENERGI SAMPAH RUMAH TANGGA HASIL PEMBAKARAN INSENERATOR SISTEM KONTINYU - Subagiyo Subagiyo; Eko Naryono; Sandra Santoso; Bambang Irawan (INFO-TEKNIK, 2015)
The combustion process is one of the alternative methods of processing waste are effectively used in the processing of household organic waste. In this study used a continuous combustion incinerator system, with a flow rate of garbage 10 kg / h and a water content of 15% by the air blast rate of 1,5 - 2,5 liters / sec. Heat of combustion is used to heat water in a boiler that is monitored / measured temperature and vapor pressure. This study aimed to obtain characterization Heating (temperature vs. time) and the potential energy that can be used to heat water in a kettle containing 5 liters of water with warming from the burning of household organic waste experimentally. Based on visual observation and temperature measurement, combustion of household organic waste can produce a continuous burning about 30 minutes, and the temperature between 350-400oC on the outer side walls of the boiler / closest to the combustion chamber, the water in the kettle boiling (100 ° C) after about 25 minutes, from the observed data can be calculated energy that can be utilized for heating is from about 5000 KJ of energy generated from waste incineration, 2000 to 3000 KJ can be used for heating water in a 5 liter boiler. Keywords: Potential energy, household waste, incinerator, the system continuously.